Preparation method of moisture-curing alkoxy silicon-terminated polyacrylate sealant

CN119592269AActive Publication Date: 2025-03-11JIANGSU RUIYANG ANTAI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411759359.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

[0003]硅烷封端聚醚树脂最为广泛的应用是作为组分配制成硅烷封端聚醚密封胶,能够解决行业内现在使用的硅酮胶的许多缺点,包括固化时产生刺激性气味、表面不可涂刷、渗油等问题

Benefits of technology

[0081] Finally, the wet curable silane is introduced using 1-propylene thiol-2-dimethoxysilane, thereby obtaining the hydrosilane described in the previous process. The hydrogen silane also has a silane-capped polyether segment, which can hydrolyze to form Si-OH under the action of moisture, and can form chemical bonds or hydrogen bonds with the substrate, enhance the adhesion of the sealant to the substrate, the mechanical properties of the sealant, low temperature resistance, heat resistance and water resistance, so that its durability can be improved. Hydrosilane has a branched structure and reacts with diallyl cyclosulfur resin to form an epoxy resin component with a branched structure, and the crosslinking degree in the sealant system is increased, which directly affects the modulus and strength of the sealant, and improves its mechanical properties and heat resistance. Combining the ring sulfur group, the long chains of the crosslinked chains are combined with the short chains to form an interpenetrating network in the sealant system, which makes the sealant have better mechanical properties and durable use ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167186210000221
    Figure BDA0005167186210000221
Patent Text Reader

Abstract

The invention discloses a preparation method of a moisture-curing alkoxy silicon-terminated polyacrylate sealant, and relates to the technical field of silane-terminated polyether sealers.The preparation method comprises the following processes that firstly, alkoxy silicon-terminated polyacrylate is taken and mixed with calcium carbonate, and heating is conducted; adding a dewatering agent, stirring and mixing to obtain a first mixed material; 2, amino siloxane, an epoxy curing agent and an ultraviolet light absorber are added into the first mixed material, vacuum stirring is performed for 30-60 min, and a second mixed material is obtained; 3, the second mixed material, epoxy siloxane, epoxy resin, the flexibilizer, the filler, the catalyst and the promoter are subjected to vacuum mixing at the temperature of 30-65 DEG C, and the sealant is obtained, no toxic or harmful gas is generated in the curing process, the problems of construction safety and slow deep curing in cold days are solved, and the sealant is high in base material bonding force, capable of being brushed and good in usability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silane-terminated polyether sealants, in particular to a method for preparing moisture-cured alkoxysilane-terminated polyacrylate sealants. Background Art

[0002] Silane-terminated polyether resin is a technical product that uses silane-terminated agents containing active groups to terminate polyether. The advantages of this resin are: after curing, it releases colorless and odorless small molecule alcohol substances, which is safer and more environmentally friendly, and has excellent properties such as good surface paintability. Since silane-terminated polyether resin is a silane-modified polyether material, the performance of this resin combines the dual advantages of silicone and polyurethane, making the material itself have better weather resistance and the strength of the colloid produced.

[0003] The most widely used application of silane-terminated polyether resin is as a component to prepare silane-terminated polyether sealant, which can solve many shortcomings of silicone glue currently used in the industry, including pungent odor during curing, unpaintable surface, oil seepage and other problems. At the same time, compared with polyurethane glue, silane-terminated polyether sealant has better weather resistance, does not contain free isocyanate, does not contain organic solvents, etc. This type of silane-terminated polyether sealant combines the advantages of silicone glue and polyurethane glue to the maximum extent, while avoiding the shortcomings of silicone glue and polyurethane glue, such as lack of environmental protection, poor storage resistance, narrow scope of use, etc. Its performance has been comprehensively improved and can be widely used in various fields. The development of silane-terminated polyether sealant has greatly enriched the prospects of high-end sealants in the world.

[0004] At present, this type of colloid belongs to the high-end adhesive variety on the market, and the main raw material suppliers are mostly from large foreign companies such as Wacker, Covestro, and Evonik. In various industrial production activities in my country, the development of domestic sealants started late, and most high-end sealants need to be imported. The academic research and industrial transformation of new sealants are still to be improved. With the continuous prosperity of my country's economy, the market demand for high-performance sealants can be expected to increase further. Relevant researchers need to further explore the synthesis mechanism and preparation method of silane-modified polymers, pursue more advanced production processes, and achieve better comprehensive performance. Therefore, we propose a preparation method for moisture-curing alkoxysilane-terminated polyacrylate sealant. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0007] Step 1: Take alkoxysilane-terminated polyacrylate, mix it with calcium carbonate, and heat it; add a dehydrating agent, stir and mix, and obtain a first mixed material;

[0008] Step 2: Add aminosiloxane, epoxy curing agent and ultraviolet absorber to the first mixed material obtained in step 1, and stir under vacuum for 30 to 60 minutes to obtain a second mixed material;

[0009] Step 3: Mix the second mixed material obtained in step 2, epoxysiloxane, epoxy resin, toughening agent, filler, catalyst and accelerator in a vacuum at 30-65° C. to obtain a sealant.

[0010] Furthermore, the sealant includes the following components by mass: 100 parts of alkoxysilicon-terminated polyacrylate, 50 to 200 parts of calcium carbonate, 3 to 10 parts of dewatering agent, 0.2 to 3.0 parts of aminosiloxane, 18 to 40 parts of epoxy curing agent, 0.1 to 1.0 parts of ultraviolet absorber, 0.2 to 3.0 parts of epoxysiloxane, 50 to 100 parts of epoxy resin, 20 to 30 parts of toughening agent, 20 to 75 parts of filler, 0.1 to 1.0 parts of catalyst, and 1.0 to 2.5 parts of accelerator.

[0011] Furthermore, in the step 1, the heating process is: vacuumizing for 12 hours at a temperature of 100-120°C; and then cooling to 18-40°C.

[0012] Furthermore, in step 1, the process conditions for stirring and mixing are: temperature 18-40° C., and vacuum stirring for 15-40 min.

[0013] Furthermore, the dehydrating agent is a mixture of one or more of a siloxane dehydrating agent, an oxazolidine moisture scavenger, and a molecular sieve;

[0014] The siloxane dehumidifier is one or more of vinyl trimethoxy silane, vinyl triethoxy silane and tetramethoxy silane.

[0015] Furthermore, the catalyst is an organotin compound, and the organotin compound is dibutyltin dilaurate and a chelated organotin compound;

[0016] The auxiliary promoter is a mixture of one or more of a stabilizer, an adhesion promoter, and a substrate wetting agent.

[0017] Further, the aminosiloxane is a mixture of one or more of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), N-phenyl-γ-aminopropyltriethoxysilane, N-ethyl-γ-aminopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane;

[0018] The epoxy curing agent is a mixture of one or more of a polyamide curing agent, a fatty amine curing agent, a phenolic amine curing agent, and a ketimine curing agent;

[0019] The ultraviolet absorber is a mixture of one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, and 2-(2′-hydroxy-3′,5′-di-tert-butylphenyl)-5-chlorobenzotriazole;

[0020] The epoxysiloxane is γ-(2,3-epoxypropoxy)propyltrimethoxysilane;

[0021] The epoxy resin is a mixture of one or more of bisphenol F epoxy resin, bisphenol A epoxy resin, novolac epoxy resin, o-cresol epoxy resin and tetrafunctional glycidylamine epoxy resin.

[0022] The filler is a mixture of one or more of talc, kaolin, silicon dioxide, diatomaceous earth, titanium dioxide, silicon micropowder, zinc phosphate, aluminum oxide and glass fiber.

[0023] Furthermore, the alkoxysilane-terminated polyacrylate is prepared by the following process:

[0024] At a temperature of 40 to 50° C., acrylic resin, isocyanate silane and an organic tin catalyst are mixed and reacted for 3 to 6 hours to obtain an alkoxysilane-terminated polyacrylate.

[0025] Furthermore, the alkoxysilane-terminated polyacrylate has the following components by mass: 1000-1200 parts of acrylic resin, 0.44-0.86 parts of organic tin catalyst, and 39-60 parts of isocyanate silane.

[0026] Furthermore, the alkoxysilane-terminated polyacrylate is prepared by the following process:

[0027] At a temperature of 40 to 50° C., acrylic resin, organic polyisocyanate, and 83 to 91% by weight of an organic tin catalyst are mixed and reacted for 3 to 6 hours;

[0028] The temperature is raised to 60-70° C., and then isocyanate silane is added, and the remaining organotin catalyst is added, and the reaction is continued for 2-3 hours to obtain alkoxysilane-terminated polyacrylate.

[0029] Furthermore, the alkoxysilicon-terminated polyacrylate has the following components by mass: 1000-1200 parts of acrylic resin, 4-8 parts of organic polyisocyanate, 0.44-1.25 parts of organic tin catalyst, and 39-60 parts of isocyanate silane.

[0030] Furthermore, after the alkoxysilane-terminated polyacrylate is obtained, the temperature is lowered to 20-40° C., a dehydrating agent, vinyl trimethoxy silane, is added, stirred for 30-60 minutes, and the material is discharged for later use.

[0031] Furthermore, the functionality of the polyether polyol is 2, and the number average molecular weight is 4,000 to 20,000.

[0032] Furthermore, the organic polyisocyanate is one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.

[0033] Furthermore, the isocyanate silane is isocyanate methyl triethoxy silane.

[0034] Furthermore, the organotin catalyst is dibutyltin dilaurate and a chelated organotin compound.

[0035] Furthermore, the acrylic resin is prepared by the following process:

[0036] Mixing butyl acrylate, methyl methacrylate, hydroxyethyl acrylate, mercaptoethanol and 80-90% by weight of an initiator to obtain a mixed solution;

[0037] Slowly add the mixed solution to the polyether polyol and add it over 3 to 5 hours; after the addition is completed, keep warm and react for 1 to 2 hours; add the remaining initiator and continue to react for 1 to 2 hours;

[0038] The temperature is raised to 120-130° C., and vacuum is applied for 1-3 hours to remove unreacted mercaptoethanol; the temperature is lowered to 40-60° C., and the material is discharged to obtain acrylic resin.

[0039] Further, the acrylic resin includes the following components by mass: 1000 parts of polyether polyol, 100 to 200 parts of mixed liquid;

[0040] The mixed liquid comprises the following components by mass: 600-800 parts of butyl acrylate, 50-150 parts of methyl methacrylate, 10-20 parts of hydroxyethyl acrylate, 5.5-12.0 parts of initiator and 5-10 parts of mercaptoethanol.

[0041] Furthermore, the polyether polyol is dehydrated before use; then cooled to 30-50° C., organic polyisocyanate is added and mixed, heated to 65-75° C., reacted for 2-4 hours, and the product is recorded as a hydroxyl-terminated prepolymer.

[0042] Furthermore, the mixing temperature is 35-45°C, and the reaction temperature is 70-75°C.

[0043] Furthermore, the amount of organic polyisocyanate used is 0.4% to 1.5% of the mass of the polyether polyol.

[0044] Furthermore, in the preparation components of alkoxysilane-terminated polyacrylate, when a hydroxyl-terminated prepolymer is used to replace the polyether polyol, the amount of isocyanate silane is 2% to 5% of the hydroxyl-terminated prepolymer, and more optimally 3% to 4%;

[0045] The addition temperature of isocyanate silane is 40-60°C, and the more optimized temperature is 50-55°C;

[0046] The reaction time after the addition of the isocyanate silane is 2 to 4 hours.

[0047] Furthermore, the dehydration process of the polyether polyol is: heating to 100-130° C., vacuuming for 1-3 hours; and the water content after dehydration is below 200 ppm.

[0048] In the above technical scheme, polyether polyol is reacted with acrylic monomer to prepare acrylic resin; then the acrylic resin is reacted with siloxane and mixed with other components to obtain alkoxysilicon-terminated polyacrylate sealant material, which does not contain free isocyanate and can effectively prevent the foaming of the sealant. After the resin is cured, small molecule alcohol substances are released, which have low Voc emission characteristics, are environmentally friendly and pollution-free, and have fast deep curing and can be used for bonding and sealing between structures. The cured product has high modulus, high strength, and a certain elongation at break, and has good usability as a bonding and sealing material.

[0049] Alkoxysilane-terminated polyacrylate and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792) were mixed evenly. After one week of moisture curing in the air, the modulus of the obtained gel was 0.4MPa-1.0MPa, with a relatively low Young's modulus. The colloid had good water compatibility and mechanical properties, and had good adhesion to the moist substrate. The prepared sealant had higher elasticity, could better adapt to the sealing shape and deformation conditions, and was conducive to improving the sealing performance of the sealant. It could also improve stress transfer, relieve stress concentration, avoid the risk of fracture caused by stress concentration, and improve fatigue life. The appropriate modulus could prevent the prepared sealant from having too high elasticity, extrusion, and flow, which would affect its sealing performance and service life.

[0050] In the above technical scheme, epoxy resin, epoxy curing agent and epoxy siloxane are also added to the sealant components, which can participate in curing, play the role of film-forming agent, have good adhesion and thermal stability, and cooperate with alkoxy silicon-terminated polyacrylate to increase the bonding strength between the prepared sealant and the substrate and improve its service life.

[0051] The introduction of toughening agent can alleviate the brittleness of epoxy resin and its curing system, improve the toughness and impact resistance of the sealant, and improve its resistance to external impact and vibration during use. The use of filler can significantly improve the mechanical properties of sealant, reduce the amount of resin, reduce costs, adjust the physical properties of sealant such as thermal expansion coefficient, thermal conductivity, heat resistance, etc., and can also improve thixotropy, adjust the fluidity of the glue, and facilitate operation and processing.

[0052] Furthermore, the epoxy resin can be replaced by an organosiliconized episulfide resin, which is specifically prepared by the following process:

[0053] Mix diallyl episulfide resin, hydrosilane and toluene, heat to 30-50° C., add a platinum catalyst, raise the temperature to 70-75° C., and react at a constant temperature for 65-120 minutes to obtain an organosiliconized episulfide resin.

[0054] Furthermore, the molar ratio of the allyl double bond in the diallyl episulfide resin to the silicon-hydrogen bond in the hydrosilane is 1:(1.1-1.2);

[0055] The platinum catalyst is a chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid used is 1 / 4200 to 1 / 2100 of the amount of the allyl double bond substance;

[0056] The ratio of diallyl episulfide resin to toluene was 80 g / 100 mL.

[0057] In the above technical scheme, affected by its own characteristics, the epoxy resin is relatively brittle after curing, with concentrated thermal stress, easy to delaminate at low temperature, and almost zero adhesion to wet substrates. Therefore, an episulfide resin containing allyl double bonds is selected, and it is added with hydrogen silane under the action of platinum catalyst to introduce a moisture-curable silane structure, so that the epoxy resin component (organic siliconized episulfide resin) has better water compatibility and mechanical properties, which can improve the adhesion of the epoxy resin component to the wet substrate, help improve stress transfer, and improve the fatigue resistance of the sealant. In addition, the modification of epoxy resin by silicone improves the structure of the epoxy resin molecular chain, effectively improves its toughness, reduces viscosity, and helps improve its mechanical properties, processing fluidity, low temperature resistance, heat resistance, water resistance and other capabilities.

[0058] Further, the diallyl episulfide resin is prepared by the following process:

[0059] Mix 4,4'-diallyl bisphenol A, epichlorohydrin and tetramethylammonium bromide, and heat to 90-100°C for reaction for 100-150 minutes under nitrogen atmosphere protection; cool to 80-85°C, slowly add sodium hydroxide solution, and continue to react for 30-40 minutes; remove excess epichlorohydrin by reduced pressure distillation at 120°C, add toluene to dissolve, wash with deionized water, add alkali solution, react at 80-90°C for 100-150 minutes, adjust the pH of the system to neutral, wash with water, and remove toluene by distillation to obtain diallyl bisphenol A type epoxy resin;

[0060] Deionized water and ethanol are mixed, diallyl bisphenol A epoxy resin and 88-91% of the component mass of potassium thiocyanate are added, and the reaction is carried out at a temperature of 30-35°C for 60-90 minutes; the remaining potassium thiocyanate is added, and the reaction is continued for 150-200 minutes; chloroform is added to separate the layers, the lower organic phase is taken out, washed with water until neutral, separated and dried with anhydrous sodium sulfate, filtered, and rotary evaporated to obtain diallyl episulfide resin.

[0061] Further, the mass ratio of 4,4'-diallyl bisphenol A, epichlorohydrin, and tetramethylammonium bromide is (31-35):100:(1.0-1.1);

[0062] The ratio of 4,4'-diallylbisphenol A and sodium hydroxide solution (48 wt%) is 100 g: (50-55) mL;

[0063] The alkali solution is 5wt% sodium hydroxide solution.

[0064] Furthermore, the mass ratio of diallyl bisphenol A epoxy resin to potassium thiocyanate is 1:(1.0-1.1);

[0065] The ratio of diallyl bisphenol A type epoxy resin, deionized water and ethanol is 10: (255-260) mL: (516-688) mL.

[0066] In the above technical scheme, 4,4'-diallylbisphenol A reacts with epichlorohydrin in the presence of a catalyst tetramethylammonium bromide and is epoxidized to obtain a diallylbisphenol A type epoxy resin; potassium thiocyanate is then used to epsulfurize the epoxy group to form a diallyl episulfide resin. While retaining the double bonds required for hydrosilylation, an episulfide group is obtained. Compared with the epoxy group, the bond length and bond angle are larger, the reactivity is better, and the epoxy resin component (siliconized episulfide resin) in the sealant can be promoted to have a faster curing speed, higher low-temperature reaction activity, and lower shrinkage. The cured product has a higher glass transition temperature, heat resistance and mechanical properties; the water resistance is better, the interaction energy with the substrate is lower, and the prepared sealant has better wettability and adhesion to the substrate.

[0067] Further, the hydrosilane is prepared by the following process:

[0068] Mix the dithiophenyl ether compound with a sodium hydroxide solution, heat it to 38-43° C., add 3,5-dichloronitrobenzene, and reflux for 5-6 hours; extract with ethyl acetate, combine the oil layers, acidify, filter, wash with water, and dry to obtain a phenylene sulfide compound;

[0069] The phenylene sulfide compound, palladium / carbon catalyst and anhydrous ethanol are mixed, the temperature is raised to 70-75°C, hydrazine hydrate is slowly added, and the reaction is refluxed for 7-8 hours; activated carbon is added for decolorization for 15-20 minutes, the catalyst and activated carbon are removed by hot filtration, distilled water is added, suction is filtered, and recrystallization is performed using methanol and water to obtain an aminophenylene sulfide compound;

[0070] The aminophenyl sulfide compound, bismaleimide-diethylene glycol and isopropanol are mixed, a catalyst is added, and the mixture is heated to 83-88° C. and refluxed for 12-36 hours; 1-propanethiol-2-dimethoxysilane is added and the reaction is continued for 12-16 hours; and distilled under reduced pressure, washed and dried to obtain hydrosilane.

[0071] Further, the dithiophenyl ether compound is a mixture of one or more of 4,4'-dithiodiphenyl ether, 4,4-dithiodiphenyl sulfide, and 4,4'-thiobis[3,5-dimethyl]-benzenethiol (CAS No. 599164-35-9);

[0072] The molar ratio of dithiophenyl ether compound and 3,5-dichloronitrobenzene is (1.2-2.0):1;

[0073] The molar ratio of the dithiophenyl ether compound to sodium hydroxide is 1:(2.0-2.1); the concentration of the sodium hydroxide solution is 13-15%.

[0074] Further, the mass ratio of the phenylene sulfide compound, hydrazine hydrate, and palladium / carbon catalyst is 10:(16-18):(0.25-0.35);

[0075] The ratio of the phenyl sulfide compound to anhydrous ethanol is (8 to 9) g / 100 mL.

[0076] Further, the mass ratio of aminophenyl sulfide compound, bismaleimide-diethylene glycol (CAS No. 1070882-80-2), and 1-propanethiol-2-dimethoxysilane (CAS No. 94099-12-4) is 1: (1.68-1.77): (0.62-0.66);

[0077] The catalyst is BF 3 ·OEt 2 , the dosage is 5.0-6.5% of the mass of aminophenyl sulfide;

[0078] The ratio of the aminophenyl sulfide compound to isopropyl alcohol is (5 to 10) g / 100 mL.

[0079] In the above technical scheme, a dithiophenyl ether compound is reacted with 3,5-dichloronitrobenzene to obtain a phenylene sulfide compound; the formation of a phenylene sulfide chain segment can significantly improve the strength of the epoxy resin component, and help improve the mechanical properties and water and heat resistance of the prepared sealant.

[0080] Then, the nitro group (3,5-dichloronitrobenzene residue) in its structure is converted into an amino group to obtain a phenylene sulfide compound with an amino side chain, which is recorded as an aminophenylene sulfide compound and has multifunctionality that can undergo double bond addition; the product is added with maleimide in bismaleimide-diethylene glycol to improve the cohesive strength of the epoxy resin component, enhance the toughness of the epoxy resin component, and improve the strength and high temperature resistance of the sealant, which is beneficial to the improvement of its mechanical properties and heat resistance, the reduction of processing difficulty, the improvement of durability, and the improvement of service life and reliability.

[0081] Finally, 1-propanethiol-2-dimethoxysilane is used to introduce moisture-curable silane, so as to obtain the hydrogen silane described in the previous process. The hydrogen silane also has a silane-terminated polyether segment, which can be hydrolyzed to form Si-OH under the action of moisture, and can form a chemical bond or hydrogen bond with the substrate, thereby enhancing the adhesion of the sealant to the substrate, the mechanical properties of the sealant, and the low temperature resistance, heat resistance, and water resistance, thereby improving its durability. Hydrogen silane has a branched structure, reacts with a diallyl episulfide resin, and the epoxy resin component formed has a branched structure, and the crosslinking degree in the sealant system is improved, which directly affects the modulus and strength of the sealant, and improves its mechanical properties and heat resistance. Combined with the episulfide group, the long chain of the crosslinked chain is combined with the short chain to form an interpenetrating network in the sealant system, which makes the prepared sealant have more excellent mechanical properties and durable use ability. DETAILED DESCRIPTION

[0082] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0083] In the following specific embodiments, the "parts" are all parts by mass;

[0084] The dewatering agent is a siloxane dewatering agent vinyl trimethoxy silane;

[0085] The catalyst is an organic tin compound, and the organic tin compound is dibutyltin dilaurate;

[0086] The co-accelerator is a mixture of stabilizer Tinuvin 770DF, adhesion promoter ADP and substrate wetting agent TEGO 245.

[0087] The aminosiloxane is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane;

[0088] The epoxy curing agent is a mixture of polyamide curing agent EPIKURE 3175, polyetheramine curing agent D230, and phenalkamine curing agent T31, with a mass ratio of 4.5:1:1.2, which are from Hansen, Huntsman, and Tianjin Sanhe, respectively;

[0089] The ultraviolet absorber is a mixture of 2,4-dihydroxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, and 2-(2′-hydroxy-3′,5′-di-tert-butylphenyl)-5-chlorobenzotriazole in a mass ratio of 2:1:1;

[0090] The epoxysiloxane is γ-(2,3-epoxypropoxy)propyltrimethoxysilane;

[0091] Epoxy resin: Bisphenol A epoxy resin CYD-128, from China Petrochemical Corporation Baling Branch;

[0092] The toughening agent is polytetramethylene ether glycol bis-p-aminobenzoate;

[0093] The fillers include light calcium carbonate LJ-1250, heavy calcium carbonate LJ-800 and titanium dioxide B101-B, with a mass ratio of 100:55:15, all from Shanghai Liangjiang Titanium Dioxide Chemical Products Co., Ltd.;

[0094] Polyether polyol: DL-18000 has a functionality of 2, a number average molecular weight of 8000, and a GPC molecular weight distribution of 1.1. It is sourced from Shandong Bluestar Dongda Co., Ltd. The polyether polyol was dehydrated before use. The process was as follows: heating to 110°C, vacuuming for 3 hours, and the water content after dehydration was below 200 ppm.

[0095] The organic polyisocyanate was hexamethylene diisocyanate, sourced from BASF;

[0096] The isocyanate silane is isocyanate methyl triethoxy silane;

[0097] The organotin catalyst is dibutyltin dilaurate;

[0098] Calcium carbonate: Nano calcium carbonate, sourced from Ruicheng Xintai Nanomaterials Co., Ltd.;

[0099] Palladium / carbon catalyst: 10% Pd, from Sinopharm Chemical Reagent Co., Ltd.;

[0100] Chloroplatinic acid / isopropanol solution: Pt content 1000ppm, sourced from Beijing Bailingwei Technology Co., Ltd.;

[0101] Diallyl episulfide resin is prepared by the following process:

[0102] 4,4'-diallylbisphenol A, epichlorohydrin and tetramethylammonium bromide were mixed, and the temperature was raised to 95°C for reaction for 120 minutes under the protection of nitrogen atmosphere; the temperature was lowered to 82°C, and sodium hydroxide solution was slowly added, and the reaction was continued for 35 minutes; excess epichlorohydrin was removed by reduced pressure distillation at 120°C, toluene was added to dissolve, and deionized water was washed, and 5wt% sodium hydroxide solution was added, and the reaction was carried out at 85°C for 120 minutes, and the pH of the system was adjusted to neutral, and the mixture was washed with water and toluene was removed by distillation to obtain diallylbisphenol A type epoxy resin; the mass ratio of 4,4'-diallylbisphenol A, epichlorohydrin and tetramethylammonium bromide was 33:100:1.05; the ratio of 4,4'-diallylbisphenol A and sodium hydroxide solution (48wt%) was 100g:52mL;

[0103] Mix deionized water and ethanol, add diallyl bisphenol A epoxy resin and 90% of the component mass of potassium thiocyanate, and react at 32°C for 75 minutes; add the remaining potassium thiocyanate and continue to react for 180 minutes; add chloroform to separate, take out the lower organic phase and wash it with water until it is neutral, separate the liquids and dry it with anhydrous sodium sulfate, filter it, and rotary evaporate it to obtain an episulfide resin; the mass ratio of diallyl bisphenol A epoxy resin to potassium thiocyanate is 1:1.05; the ratio of diallyl bisphenol A epoxy resin, deionized water, and ethanol is 10:258mL:602mL;

[0104] After the alkoxysilane-terminated polyacrylate is prepared, the temperature is lowered to 30° C., 3% of a dehydrating agent, vinyl trimethoxy silane, is added, stirred for 30 minutes, and then discharged.

[0105] Example 1: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0106] (1) 600 parts of butyl acrylate, 100 parts of methyl methacrylate, 20 parts of hydroxyethyl acrylate, 10 parts of mercaptoethanol and 5 parts of initiator are mixed to obtain a mixed solution; 160 parts of the mixed solution are slowly added to 1000 parts of polyether polyol over 5 hours; after the addition is completed, the mixture is kept warm for reaction for 1 hour; 1 part of initiator is added and the reaction is continued for 1 hour; the temperature is raised to 120° C. and vacuumed for 3 hours to remove unreacted mercaptoethanol, thereby obtaining an acrylic resin;

[0107] (2) cooling to 40° C., adding 45.57 parts of isocyanate silane and 0.51 parts of an organic tin catalyst, and reacting for 6 hours to obtain an alkoxysilane-terminated polyacrylate;

[0108] (3) taking alkoxysilane-terminated polyacrylate, mixing it with calcium carbonate, and evacuating it at 100° C. for 12 hours; cooling it to 18° C.; adding a dehydrating agent, stirring and mixing to obtain a first mixed material; adding aminosiloxane, epoxy curing agent and ultraviolet absorber, and vacuum stirring for 30 minutes to obtain a second mixed material;

[0109] The second mixed material, epoxysiloxane, epoxy resin, toughening agent, filler, catalyst and promoter are mixed in vacuum at 30°C to obtain a sealant; the moisture-curing alkoxysilicon-terminated polyacrylate sealant includes the following components by mass: 100 parts of alkoxysilicon-terminated polyacrylate, 120 parts of calcium carbonate, 7 parts of dehydrating agent, 3.0 parts of aminosiloxane, 18 parts of epoxy curing agent, 0.5 parts of ultraviolet absorber, 3.0 parts of epoxysiloxane, 50 parts of epoxy resin, 20 parts of toughening agent, 50 parts of filler, 0.5 parts of catalyst and 1.5 parts of promoter.

[0110] Example 2: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0111] (1) 600 parts of butyl acrylate, 100 parts of methyl methacrylate, 20 parts of hydroxyethyl acrylate, 10 parts of mercaptoethanol and 5 parts by weight of initiator are mixed to obtain a mixed solution; 200 parts of the mixed solution are slowly added to 1000 parts of polyether polyol over 4 hours; after the addition is completed, the mixture is kept warm for reaction for 1.5 hours; 1 part of initiator is added and the reaction is continued for 1.5 hours; the temperature is raised to 125° C. and vacuumed for 2 hours to remove unreacted mercaptoethanol; the temperature is lowered to 50° C. and the mixture is discharged to obtain an acrylic resin;

[0112] (2) adding 51.42 parts of isocyanate silane and 0.51 parts of an organotin catalyst, mixing, and reacting for 4.5 hours to obtain an alkoxysilane-terminated polyacrylate;

[0113] (3) taking alkoxysilane-terminated polyacrylate, mixing it with calcium carbonate, and evacuating it at 110° C. for 12 h; cooling it to 25° C.; adding a dehydrating agent, stirring and mixing to obtain a first mixed material; adding aminosiloxane, epoxy curing agent and ultraviolet absorber, and stirring in vacuum for 45 min to obtain a second mixed material;

[0114] The second mixed material, epoxysiloxane, epoxy resin, toughening agent, filler, catalyst and promoter are vacuum mixed at 45°C to obtain a sealant; the moisture-curing alkoxysilicon-terminated polyacrylate sealant includes the following components by mass: 100 parts of alkoxysilicon-terminated polyacrylate, 120 parts of calcium carbonate, 7 parts of dehydrating agent, 1.5 parts of aminosiloxane, 30 parts of epoxy curing agent, 0.5 parts of ultraviolet absorber, 1.5 parts of epoxysiloxane, 75 parts of epoxy resin, 25 parts of toughening agent, 50 parts of filler, 0.5 parts of catalyst, and 1.5 parts of promoter.

[0115] Example 3: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0116] (1) 800 parts of butyl acrylate, 150 parts of methyl methacrylate, 15 parts of hydroxyethyl acrylate, 15 parts of mercaptoethanol and 8 parts of initiator are mixed to obtain a mixed solution; 200 parts of the mixed solution are slowly added to 1000 parts of polyether polyol over 3 hours; after the addition is completed, the mixture is kept warm for reaction for 2 hours; 2 parts of initiator are added and the reaction is continued for 2 hours; the temperature is raised to 130° C. and vacuumed for 1 hour to remove unreacted mercaptoethanol; the temperature is lowered to 60° C. and the mixture is discharged to obtain an acrylic resin;

[0117] (2) adding 45.57 parts of isocyanate silane and 0.51 parts of an organotin catalyst, mixing and reacting for 3 hours to obtain an alkoxysilane-terminated polyacrylate;

[0118] (3) taking alkoxysilane-terminated polyacrylate, mixing it with calcium carbonate, and evacuating it at 120° C. for 12 hours; cooling it to 40° C.; adding a dehydrating agent, stirring and mixing to obtain a first mixed material; adding aminosiloxane, epoxy curing agent and ultraviolet absorber, and stirring in vacuum for 60 minutes to obtain a second mixed material;

[0119] The second mixed material, epoxysiloxane, epoxy resin, toughening agent, filler, catalyst and promoter are vacuum mixed at 65°C to obtain a sealant; the moisture-curing alkoxysilicon-terminated polyacrylate sealant includes the following components by mass: 100 parts of alkoxysilicon-terminated polyacrylate, 120 parts of calcium carbonate, 7 parts of dehydrating agent, 0.2 parts of aminosiloxane, 40 parts of epoxy curing agent, 0.5 parts of ultraviolet absorber, 0.2 parts of epoxysiloxane, 100 parts of epoxy resin, 30 parts of toughening agent, 50 parts of filler, 0.5 parts of catalyst and 1.5 parts of promoter.

[0120] Example 4: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0121] (1) 600 parts of butyl acrylate, 100 parts of methyl methacrylate, 20 parts of hydroxyethyl acrylate, 10 parts of mercaptoethanol and 5 parts of initiator are mixed to obtain a mixed solution; 100 parts of the mixed solution are slowly added to 1000 parts of polyether polyol over 5 hours; after the addition is completed, the mixture is kept warm for reaction for 1 hour; 1 part of initiator is added and the reaction is continued for 1 hour; the temperature is raised to 120° C. and vacuumed for 3 hours to remove unreacted mercaptoethanol, thereby obtaining an acrylic resin;

[0122] (2) cooling to 40° C., adding 45.57 parts of isocyanate silane and 1.0 parts of an organic tin catalyst, and reacting for 6 hours; discharging the material to form a prepolymer, and obtaining an alkoxysilane-terminated polyacrylate;

[0123] Step (3) is the same as in Example 1 to obtain a sealant.

[0124] Example 5: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0125] (3) Mixing the dithiophenyl ether compound with a 13% sodium hydroxide solution, heating to 38° C., adding 3,5-dichloronitrobenzene, and reflux for 5 hours; extracting with ethyl acetate, combining the oil layers, acidifying, filtering, washing with water, and drying to obtain a phenylene sulfide compound; the dithiophenyl ether compound is 4,4'-dithiodiphenyl ether; the molar ratio of the dithiophenyl ether compound to 3,5-dichloronitrobenzene is 2:1; the molar ratio of the dithiophenyl ether compound to sodium hydroxide is 1:2;

[0126] A phenylene sulfide compound, a palladium / carbon catalyst and anhydrous ethanol are mixed, the temperature is raised to 70°C, hydrazine hydrate is slowly added, and the reaction is refluxed for 7 hours; activated carbon is added for decolorization for 15 minutes, the catalyst and activated carbon are removed by hot filtration, distilled water is added, suction is filtered, and recrystallization is performed using methanol and water to obtain an aminophenylene sulfide compound; the mass ratio of the phenylene sulfide compound, hydrazine hydrate and palladium / carbon catalyst is 10:16:0.25; the ratio of the phenylene sulfide compound to anhydrous ethanol is 8.5 g / 100 mL;

[0127] The aminophenyl sulfide compound, bismaleimide-diethylene glycol and isopropanol were mixed, a catalyst was added, and the mixture was heated to 83°C and refluxed for 12 hours; 1-propanethiol-2-dimethoxysilane was added and the reaction was continued for 12 hours; the mixture was distilled under reduced pressure, washed and dried to obtain hydrosilane; the mass ratio of the aminophenyl sulfide compound, bismaleimide-diethylene glycol and 1-propanethiol-2-dimethoxysilane was 1:1.68:0.62; the catalyst was BF 3 ·OEt 2 , the dosage is 5.0% of the mass of aminophenyl sulfide; the ratio of aminophenyl sulfide compound to isopropanol is 10g / 100mL;

[0128] Mix diallyl episulfide resin, hydrosilane and toluene, heat to 30°C, add platinum catalyst; heat to 70°C, and react at constant temperature for 65 minutes to obtain organosiliconized episulfide resin; the molar ratio of allyl double bond and silicon-hydrogen bond is 1:1.1; the platinum catalyst is chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid is 1 / 4200 of the amount of allyl substance; the ratio of diallyl episulfide resin to toluene is 80g / 100mL;

[0129] Steps (1-2, 4) are the same as (1-3) in Example 1, except that the epoxy resin is replaced by an organosiliconized episulfide resin to obtain a sealant.

[0130] Example 6: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0131] (1) 600 parts of butyl acrylate, 100 parts of methyl methacrylate, 20 parts of hydroxyethyl acrylate, 10 parts of mercaptoethanol and 5 parts of initiator are mixed to obtain a mixed solution; the polyether polyol is dehydrated before use; then the temperature is lowered to 30° C., an organic polyisocyanate (1.0% by mass of the polyether polyol) is added, mixed at 40° C., heated to 70° C., and reacted for 3 hours to obtain a hydroxyl-terminated prepolymer; 160 parts of the mixed solution are slowly added to 1000 parts of the hydroxyl-terminated prepolymer over 5 hours; after the addition is completed, the mixture is kept warm for reaction for 1 hour; 0.5 parts of initiator are added, and the reaction is continued for 1 hour; the temperature is raised to 120° C., and vacuum is applied for 3 hours to remove unreacted mercaptoethanol to obtain an acrylic resin;

[0132] (2) cooling to 55° C., adding 45.57 parts of isocyanate silane and 0.51 parts of an organic tin catalyst, and reacting for 4 hours to obtain an alkoxysilane-terminated polyacrylate;

[0133] (3) Mixing the dithiophenyl ether compound with a 14% sodium hydroxide solution, heating to 40° C., adding 3,5-dichloronitrobenzene, and reflux reaction for 5.5 hours; extracting with ethyl acetate, combining the oil layers, acidifying, filtering, washing with water, and drying to obtain a phenylene sulfide compound; the dithiophenyl ether compound is 4,4-dithiodiphenyl sulfide; the molar ratio of the dithiophenyl ether compound to 3,5-dichloronitrobenzene is 1.6:1; the molar ratio of the dithiophenyl ether compound to sodium hydroxide is 1:2.05;

[0134] The phenylene sulfide compound, the palladium / carbon catalyst and the anhydrous ethanol were mixed, the temperature was raised to 72°C, hydrazine hydrate was slowly added, and the reaction was refluxed for 7.5 hours; activated carbon was added for decolorization for 18 minutes, the catalyst and activated carbon were removed by hot filtration, distilled water was added, suction was filtered, and the aminophenylene sulfide compound was obtained by recrystallization using methanol and water; the mass ratio of the phenylene sulfide compound, hydrazine hydrate and the palladium / carbon catalyst was 10:17:0.30; the ratio of the phenylene sulfide compound and the anhydrous ethanol was 8.5 g / 100 mL;

[0135] The aminophenyl sulfide compound, bismaleimide-diethylene glycol and isopropanol were mixed, a catalyst was added, and the mixture was heated to 85°C and refluxed for 24 hours; 1-propanethiol-2-dimethoxysilane was added and the reaction was continued for 14 hours; the mixture was distilled under reduced pressure, washed and dried to obtain hydrosilane; the mass ratio of the aminophenyl sulfide compound, bismaleimide-diethylene glycol and 1-propanethiol-2-dimethoxysilane was 1:1.72:0.64; the catalyst was BF 3 ·OEt 2 , the dosage is 5.8% of the mass of aminophenyl sulfide; the ratio of aminophenyl sulfide compound to isopropanol is 8g / 100mL;

[0136] Mix diallyl episulfide resin, hydrosilane and toluene, heat to 40°C, add platinum catalyst; heat to 72°C, and react at constant temperature for 90 minutes to obtain organosiliconized episulfide resin; the molar ratio of allyl double bonds in diallyl episulfide resin and silicon-hydrogen bonds in hydrosilane is 1:1.15; the platinum catalyst is chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid is 1 / 3100 of the amount of allyl double bond substance; the ratio of diallyl episulfide resin to toluene is 80g / 100mL;

[0137] Step (4) is the same as step (3) in Example 1, except that the epoxy resin is replaced by an organosiliconized episulfide resin to obtain a sealant.

[0138] Example 7: A method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0139] (2) adding 6 parts of organic polyisocyanate and 0.85 parts of organic tin catalyst, and reacting for 3.5 hours; heating to 65° C., then adding 39 parts of isocyanate silane, adding 0.15 parts of organic tin catalyst, and continuing to react for 2.5 hours to obtain alkoxysilane-terminated polyacrylate;

[0140] (3) Mixing the dithiophenyl ether compound with a 15% sodium hydroxide solution, heating to 43° C., adding 3,5-dichloronitrobenzene, and reflux for 6 hours; extracting with ethyl acetate, combining the oil layers, acidifying, filtering, washing with water, and drying to obtain a phenylene sulfide compound; the dithiophenyl ether compound is 4,4'-thiobis[3,5-dimethyl]-benzenethiol; the molar ratio of the dithiophenyl ether compound to 3,5-dichloronitrobenzene is 1.2:1; the molar ratio of the dithiophenyl ether compound to sodium hydroxide is 1:2.1;

[0141] A phenylene sulfide compound, a palladium / carbon catalyst and anhydrous ethanol are mixed, the temperature is raised to 75°C, hydrazine hydrate is slowly added, and the reaction is refluxed for 8 hours; activated carbon is added for decolorization for 20 minutes, the catalyst and activated carbon are removed by hot filtration, distilled water is added, suction is filtered, and recrystallization is performed using methanol and water to obtain an aminophenylene sulfide compound; the mass ratio of the phenylene sulfide compound, hydrazine hydrate and palladium / carbon catalyst is 10:18:0.35; the ratio of the phenylene sulfide compound to anhydrous ethanol is 8.5 g / 100 mL;

[0142] The aminophenyl sulfide compound, bismaleimide-diethylene glycol and isopropanol were mixed, a catalyst was added, and the mixture was heated to 88°C and refluxed for 36 hours; 1-propanethiol-2-dimethoxysilane was added and the reaction was continued for 16 hours; the mixture was distilled under reduced pressure, washed and dried to obtain hydrosilane; the mass ratio of the aminophenyl sulfide compound, bismaleimide-diethylene glycol and 1-propanethiol-2-dimethoxysilane was 1:1.77:0.66; the catalyst was BF3 ·OEt 2 , the dosage is 6.5% of the mass of aminophenyl sulfide; the ratio of aminophenyl sulfide compound to isopropanol is 5g / 100mL;

[0143] Mix diallyl episulfide resin, hydrosilane and toluene, heat to 50°C, add platinum catalyst; heat to 75°C, and react at constant temperature for 120 minutes to obtain organosiliconized episulfide resin; the molar ratio of allyl double bonds in diallyl episulfide resin and silicon-hydrogen bonds in hydrosilane is 1:1.2; the platinum catalyst is chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid is 1 / 2100 of the amount of allyl double bond substance; the ratio of diallyl episulfide resin to toluene is 80g / 100mL;

[0144] Steps (1, 4) are the same as (1, 3) in Example 1, except that the epoxy resin is replaced by an organosiliconized episulfide resin to obtain a sealant.

[0145] Comparative Example 1: A method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0146] (3) diallyl bisphenol A epoxy resin, hydrogen silane and toluene are mixed, heated to 30° C., and a platinum catalyst is added; the temperature is raised to 70° C. and the reaction is carried out at a constant temperature for 65 minutes to obtain an organosiliconized epoxy resin; the molar ratio of allyl double bonds to silicon-hydrogen bonds is 1:1.1; the platinum catalyst is a chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid is 1 / 4200 of the amount of allyl substance; the ratio of diallyl bisphenol A epoxy resin to toluene is 80 g / 100 mL; the preparation process of hydrogen silane is the same as that in Example 5;

[0147] Steps (1-2, 4) are the same as (1-3) in Example 5, except that the epoxy resin is replaced by a siliconized epoxy resin to obtain a sealant.

[0148] Comparative Example 2: A method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0149] (3) 1-propanethiol-2-dimethoxysilane, bismaleimide-diethylene glycol and isopropanol were mixed, a catalyst was added, and the mixture was heated to 80°C and refluxed for 12 hours; the mixture was distilled under reduced pressure, washed and dried to obtain hydrosilane; the mass ratio of bismaleimide-diethylene glycol to 1-propanethiol-2-dimethoxysilane was 1:0.74; the catalyst was BF 3 ·OEt 2 , the dosage is 5.0% of the mass of bismaleimide-diethylene glycol; the ratio of bismaleimide-diethylene glycol to isopropanol is 10g / 100mL;

[0150] Mix diallyl bisphenol A epoxy resin, hydrosilane and toluene, heat to 30°C, add platinum catalyst; heat to 70°C, and react at constant temperature for 65 minutes to obtain organosiliconized epoxy resin; the molar ratio of allyl double bond and silicon-hydrogen bond is 1:1.1; the platinum catalyst is chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid is 1 / 4200 of the amount of allyl substance; the ratio of diallyl bisphenol A epoxy resin to toluene is 80g / 100mL;

[0151] Steps (1-2, 4) are the same as (1-3) in Example 5, except that the epoxy resin is replaced by a siliconized epoxy resin to obtain a sealant.

[0152] Comparative Example 3: A method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0153] (3) diallyl bisphenol A epoxy resin, trimethoxysilane and toluene are mixed, heated to 30°C, and a platinum catalyst is added; the temperature is raised to 70°C, and the reaction is carried out at a constant temperature for 65 minutes to obtain an organosiliconized epoxy resin; the molar ratio of the allyl double bond and the silicon-hydrogen bond is 1:1.1; the platinum catalyst is a chloroplatinic acid / isopropanol solution, and the amount of chloroplatinic acid is 1 / 4200 of the amount of the allyl substance; the ratio of diallyl bisphenol A epoxy resin to toluene is 80g / 100mL;

[0154] Steps (1-2, 4) are the same as (1-3) in Example 5, except that the epoxy resin is replaced by a siliconized epoxy resin to obtain a sealant.

[0155] Comparative Example 4: A method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant, comprising the following process:

[0156] (1) Mixing polyether polyol and isocyanate silane (5.0% by weight of the polyether polyol), heating to 55° C., adding 0.51 parts of an organic tin catalyst, and reacting for 4 hours; discharging the mixture to obtain an alkoxysilane-terminated polyether;

[0157] Step (2) is the same as step (3) in Example 1, except that the alkoxysilane-terminated polyacrylate is replaced by an alkoxysilane-terminated polyether to obtain a sealant.

[0158] Experiment: Take the alkoxysilane-terminated polyacrylates in Examples 1-4 and 6-7 and the alkoxysilane-terminated polyether in Comparative Example 4 as samples, and measure their viscosities at 25°C;

[0159] The sample was uniformly mixed with N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (mass ratio of 100:3), and cured for one week in humid air at 25°C and 90RH% to obtain a gel. The surface drying time (test reference GB / T13447.5 finger touch method), Shore A hardness (test reference GB / T531.1), tensile strength (dumbbell-shaped specimen, test reference GB / T528, tensile rate 500mm / min) and curing depth (tested using a curing speed plate) of the gel were tested.

[0160] Table 1, performance data of alkoxysilane-terminated polyacrylate:

[0161]

[0162] The sealants obtained in Examples 1-7 and Comparative Examples 1-4 were degassed and pressed on the surface of an aluminum sheet, and then cured and cured in humid air at 25° C. and 90 RH% for 14 days before testing.

[0163] Peel strength test: GB / T 2790 is used as the reference standard, and an electronic tensile machine is used to test the 180° peel strength of the sample;

[0164] Water resistance test: Soak the sample in a 50℃ constant temperature water bath for 7 days, take it out, wipe it dry with filter paper, test the peel strength of the sample, and calculate its water immersion reduction rate;

[0165] High and low temperature resistance test: Place the sample in a high and low temperature test chamber for high and low temperature cycle test, with 20 / ℃30min→50 / ℃30min→20 / ℃30min→50 / ℃30min→20 / ℃30min as one cycle. Test the peel strength of the sample after four cycles and calculate its high and low temperature cycle drop rate;

[0166] Tensile performance test: GB / T 528 was used as the reference standard, and the tensile performance was tested with a dumbbell-shaped specimen at a tensile speed of 50 mm / min and a test temperature of 25°C.

[0167] Table 2, sealant performance data:

[0168] Peel strength (N / mm) Water immersion drop rate (%) High and low temperature cycle drop rate (%) Tensile strength(MPa) Example 1 15.4 20.2 26.7 3.2 Example 2 18.2 21.6 28.8 3.9 Example 3 16.5 23.9 29.6 4.3 Example 4 17.8 19.3 27.0 3.0 Example 5 21.9 14.4 21.1 5.1 Example 6 24.5 12.9 18.5 5.4 Example 7 26.3 10.7 15.2 5.8 Comparative Example 1 19.2 16.4 23.7 4.7 Comparative Example 2 17.8 17.0 24.9 4.3 Comparative Example 3 16.3 18.2 26.0 3.7 Comparative Example 4 14.0 27.4 42.3 2.5

[0169] According to the data in Table 1, the following conclusions can be clearly drawn: the alkoxysilicon-terminated polyacrylates in Examples 1-4, 6-7 and the alkoxysilicon-terminated polyethers in Comparative Example 4 are compared, and the test results show that the alkoxysilicon-terminated polyacrylates in the Examples have good performance data compared with Comparative Example 4. This fully demonstrates that the present invention achieves the improvement of the processability and mechanical properties of the silane-terminated polyether resin (alkoxysilicon-terminated polyacrylate) of the sealant component.

[0170] According to the data in Table 2, the following conclusions can be clearly drawn: the sealants obtained in Examples 1-7 are compared with the sealants obtained in Comparative Examples 1-4. The test results show that compared with Examples 1-4, the epoxy resins in Examples 5-7 are modified with silicone, and the sealants obtained have higher peel strength and mechanical properties, and still maintain good peel strength after immersion in water and high and low temperature cycles. This fully demonstrates that the present invention achieves the improvement of the mechanical properties, water resistance and high and low temperature resistance of the prepared sealant, so that it has more excellent durable use ability.

[0171] Compared with Example 5, in Comparative Example 1, the organosiliconized episulfide resin is replaced by an organosiliconized epoxy resin; its reaction activity is relatively low, and under the influence of the long-chain branched structure, the crosslinking degree of the sealant system decreases, causing the performance data of the sealant to decrease. In Comparative Example 2, the organosiliconized episulfide resin is replaced by an organosiliconized epoxy resin, and its hydrogen silane is prepared from 1-propanethiol-2-dimethoxysilane and bismaleimide-diethylene glycol; the phenyl sulfide segment is not introduced into the sealant system, so that its water resistance decreases, its sensitivity to high and low temperatures increases, and its mechanical properties decrease to a certain extent. In Comparative Example 3, the organosiliconized episulfide resin is replaced by an organosiliconized epoxy resin prepared from diallyl bisphenol A type epoxy resin and trimethoxysilane. Compared with Example 1, its water resistance is improved, but compared with Example 5, it is not provided with a long chain branch, so that its water resistance is greatly reduced and its mechanical properties are also deteriorated. Compared with Example 1, in Comparative Example 4, alkoxysilicon-terminated polyacrylate was replaced with alkoxysilicon-terminated polyether, and the mechanical properties and various peel strengths decreased. It can be seen that the setting of the sealant components and the preparation process of the present invention can promote the comprehensive improvement of its mechanical properties, water resistance and high and low temperature resistance, and achieve an increase in its service life.

[0172] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant, characterized in that: Including the following processes: Step 1: Take alkoxysilane-terminated polyacrylate, mix it with calcium carbonate, and heat it; add a dehydrating agent, stir and mix, and obtain a first mixed material; Step 2: Add aminosiloxane, epoxy curing agent and ultraviolet absorber to the first mixed material obtained in step 1, and stir under vacuum for 30 to 60 minutes to obtain a second mixed material; Step 3: Mix the second mixed material obtained in step 2, epoxysiloxane, epoxy resin, toughening agent, filler, catalyst and accelerator in a vacuum at 30-65° C. to obtain a sealant.

2. The method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant according to claim 1, characterized in that: The sealant comprises the following components by mass: 100 parts of alkoxysilicon-terminated polyacrylate, 50 to 200 parts of calcium carbonate, 3 to 10 parts of dewatering agent, 0.2 to 3.0 parts of aminosiloxane, 18 to 40 parts of epoxy curing agent, 0.1 to 1.0 parts of ultraviolet absorber, 0.2 to 3.0 parts of epoxysiloxane, 50 to 100 parts of epoxy resin, 20 to 30 parts of toughening agent, 20 to 75 parts of filler, 0.1 to 1.0 parts of catalyst, and 1.0 to 2.5 parts of accelerator.

3. The method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant according to claim 1, characterized in that: The alkoxysilane-terminated polyacrylate is prepared by the following process: acrylic resin, isocyanate silane and organic tin catalyst are mixed at a temperature of 40 to 50° C. and reacted for 3 to 6 hours to obtain the alkoxysilane-terminated polyacrylate.

4. The method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant according to claim 1, characterized in that: The alkoxysilane-terminated polyacrylate is prepared by the following process: At a temperature of 40 to 50° C., acrylic resin, organic polyisocyanate, and 83 to 91% by weight of an organic tin catalyst are mixed and reacted for 3 to 6 hours; the temperature is raised to 60 to 70° C., and then isocyanate silane is added, and the remaining organic tin catalyst is added, and the reaction is continued for 2 to 3 hours to obtain alkoxy silicon-terminated polyacrylate.

5. The method for preparing a moisture-curing alkoxysilane-terminated polyacrylate sealant according to claim 3 or 4, characterized in that: The acrylic resin is prepared by the following process: Mixing butyl acrylate, methyl methacrylate, hydroxyethyl acrylate, mercaptoethanol and 80-90% by weight of an initiator to obtain a mixed solution; The mixed solution is slowly added to the polyether polyol, and the addition is completed within 3 to 5 hours. After the addition is completed, the mixture is kept warm for reaction for 1 to 2 hours. The remaining initiator is added, and the reaction is continued for 1 to 2 hours to obtain acrylic resin.

6. The method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant according to claim 5, characterized in that: The acrylic resin comprises the following components by mass: 1000 parts of polyether polyol and 100-200 parts of mixed liquid; the mixed liquid comprises the following components by mass: 600-800 parts of butyl acrylate, 50-150 parts of methyl methacrylate, 10-20 parts of hydroxyethyl acrylate, 5.5-12.0 parts of initiator and 5-10 parts of mercaptoethanol.

7. The method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant according to claim 1, characterized in that: The alkoxysilicon-terminated polyacrylate comprises the following components by mass: 1000-1200 parts of acrylic resin, 0-8 parts of organic polyisocyanate, 0.30-1.25 parts of organic tin catalyst, and 40-60 parts of isocyanate silane.

8. The method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant according to claim 1, characterized in that: The epoxy resin can be replaced by an organosiliconized episulfide resin, which is prepared by the following process: Mix diallyl episulfide resin, hydrosilane and toluene, heat to 30-50° C., add a platinum catalyst, raise the temperature to 70-75° C., and react at a constant temperature for 65-120 minutes to obtain an organosiliconized episulfide resin.

9. The method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant according to claim 8, characterized in that: The diallyl episulfide resin is prepared by the following process: Mix 4,4'-diallyl bisphenol A, epichlorohydrin and tetramethylammonium bromide, and heat to 90-100°C for reaction for 100-150 minutes under nitrogen atmosphere protection; cool to 80-85°C, slowly add sodium hydroxide solution, and continue to react for 30-40 minutes; distill under reduced pressure, add toluene, wash with water, add sodium hydroxide solution, react at 80-90°C for 100-150 minutes, adjust the pH of the system to neutral, wash with water, and distill to obtain diallyl bisphenol A type epoxy resin; Deionized water and ethanol are mixed, diallyl bisphenol A type epoxy resin and 88-91% of the component mass of potassium thiocyanate are added, and the mixture is reacted at a temperature of 30-35° C. for 60-90 minutes; the remaining potassium thiocyanate is added, and the reaction is continued for 150-200 minutes to obtain diallyl episulfide resin.

10. The method for preparing a moisture-curable alkoxysilane-terminated polyacrylate sealant according to claim 8, characterized in that: The hydrosilane is prepared by the following process: Mixing the dithiophenyl ether compound with a sodium hydroxide solution, heating to 38-43° C., adding 3,5-dichloronitrobenzene, and reflux reaction for 5-6 hours to obtain a phenylene sulfide compound; Mix a phenylene sulfide compound, a palladium / carbon catalyst and anhydrous ethanol, heat to 70-75° C., slowly add hydrazine hydrate, and reflux for 7-8 hours to obtain an aminophenylene sulfide compound; The aminophenyl sulfide compound, bismaleimide-diethylene glycol and isopropanol are mixed, a catalyst is added, and the mixture is heated to 83-88° C. and refluxed for 12-36 hours; 1-propanethiol-2-dimethoxysilane is added and the reaction is continued for 12-16 hours to obtain hydrosilane.

Citation Information

Patent Citations

  • Quick dry type polyurethane sealant and preparation method thereof

    CN105505282A

  • Organosilicon electronic pouring sealant good in impact resistance and used for PCB (printed circuit board)

    CN106634811A

  • Preparation process of flame-retardant polyester resin and application of flame-retardant polyester resin in flame-retardant coatings

    CN112592468A

  • High-strength anti-aging single-component modified sealant for bonding rubber and plastic composite materials and preparation method of high-strength anti-aging single-component modified sealant

    CN114163970A

  • Preparation method of high-temperature-resistant and strong-ultraviolet-resistant MS glue

    CN114874747A

Cited By

  • High-wear-resistance door and window material and preparation method thereof

    CN122011781A